PERANCANGAN STRATEGI PEMASARAN BERBASIS PERILAKU KONSUMEN DI TOKO SWISS JAYA, JEMBER - Karolina, .; Surjani, Rosita Meitha; Rinawiyanti, Esti Dwi (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Shop Swiss Jaya is engaged in the watch that have been able to dominate the market shareof the final consumer in Jember city itself and several retailers who resell to end customers.Business people also required to meet consumer desires so that their existence survive in toughcompetition with other businesses. Shop Swiss Jaya wants to increase sales volume by more closerto customers to determine the characteristics and desires of consumers. Consumers will beexamined are the actual consumers who have purchased the product in the store Swiss Jaya andpotential that has not been bought products in store Swiss Jaya.Spread sampling of 160 respondents and 160 respondents actual consumers of potentialcustomers. The analysis was conducted descriptive analysis, crosstabs, MANOVA analysis,quadrant analysis, SWOT analysis, design marketing strategies and marketing mix based STPD8P. Crosstabs analysis results indicate that there are differences in demographics and consumerbehavior between the actual and potential customers. The difference lies in the averageexpenditure / month (0.000), never satisfied to share the experience of others (0.022), an ordinarywall clock brand purchased (0,011), never heard / knew Swiss Clock Shop Jaya (0.000). WhileManova results indicate that there is a difference between the level of importance of actual andpotential customers (0.000). While the results of the quadrant analysis shows that the mostimportant variables entered in quadrant IV is the completeness of spare parts, provision of servicethe product at hand. Variables that are in quadrant IV is in need of repair. Quadrant analysis resultsare used to perform a SWOT analysis. Proposed marketing strategy for Swiss Stores Jaya bySTPD where segemtasinya is based on aspects of human behavior (consumer behavior). Consumerbehavior is related to the variables that most consumers in the choice of emphasis at the store tobuy the product / service. Actual Consumers Shop Swiss Jaya is most concerned about the variableproduct watches with an average interest rate of 3.977. As for the potential consumers mostconcerned about the Physical Evidence variables that have an average interest rate of 3.831.Besides Jaya Swiss Stores segment customers by region and class (upper / middle / lower).